PERUBAHAN SOSIAL MASYARAKAT MELALUI GERAKAN BANK SAMPAH: STUDI PADA BANK SAMPAH GEMAH RIPAH: KAJIAN DI DESA BADEGAN KABUPATEN BANTUL YOGYAKARTA - Yuliarso, Mohammad Zulkarnain; Purwani, Diah Ajeng (Jurnal AGRISEP, 2018)
The changes that occur in the community with the presence of the waste bank program will undoubtedly pass through a process that takes place gradually and involves the role of the independent agency that is very unusual.  Therefore, the research objectives here is to analyze the stages of changes going on in society as a result of the existence of the Waste Bank and parse variables agent role in those changes.  This research used the qualitative method with descriptive, i.e., design studies that give a picture carefully regarding certain individuals or groups about the circumstances and symptoms occur and then be matched with the prevailing theory.  Data collection is done by observation and FGD. Persistence and effort drive the large and structured society that eventually led to the results shown by the number of benefits obtained with the existence of waste bank.   The strategy that carried Gemah Ripah waste Bank to remain active up to now serve with the emphasis on children's education, do innovations, using such modern bank management, expand networks and provide socialization and accompaniment to the new waste banks.